Case study of environmental projects in Australia - Sholarin, E.; Awange, Joseph (2015)
© 2015, Springer International Publishing Switzerland. In order to share some lessons learned from conceptualization to delivery of environmental conservation and remediation projects, one case study each from Western Australia, Australian capital territory (ACT), New South Wales, Queensland, Victoria, South Australia and Tasmania has been reviewed to demonstrate the approaches to reducing environmental effects in terms of reuse and redevelopment strategy, maximum use of depleted natural resources, maximum utilization of waste products, and so on.